Vege-Grout: a Potential Bio-Grout Material from Vegetable Waste for Bio-Cementation - Omar, RC; Taha, Hairin; Roslan, R.; Baharuddin, INZ (International Journal of Engineering and Technology, 2018)
Studies have reported that the calcite precipitation induced by ureolytic bacteria through the hydrolysis of urea was influenced by several important factors including the concentration of calcium ions, the surrounding pH and temperature. Recently, the microbial induced calcite precipitations (MICP) were further explored using natural elements and microorganisms from the environment. Vegetable waste provides a proper substrate for microorganism’s growth and activities. In this study, the calcite forming ability of indigenous bacteria in the vegetable waste was investigated by mixing the extract of vegetable waste known as vege-grout with sandy soil. The vege-grout optimum content was determined by unconfined compression test to find the suitable ratio of vege-grout content. The results showed that there was an increase of compressive strength after 28 days of curing with vege-grout and significant improvement in soil shear strength. SEM and EDX analysis showed aggregation of soil particles and formation of calcium carbonate (CaCO3). Microbiological analysis of vege-grout extract indicated the presence of ureolytic bacteria that could be responsible for the bio-cementation process. ICP-MS analysis showed that the vege-grout contained a rich source of carbon, nitrogen and calcium elements. The findings have demonstrated the potential application of vegetable waste for microbial cementation of soil particles.